'A Poor but Honest Country': Corruption and Probity in Chile. Issue 2 (June 2016) - Silva, Patricio
Chile has a long record of public probity, representing an exception in Latin America. It goes back to the late colonial period when the country was ruled by relatively efficient and honest governors. During the nineteenth century, Chile built up a solid state and a stable political system, based on the rule of law. Chileans have been ever since aware of the exceptionality of their country in terms of the strength of their political institutions and the scrupulousness of their rulers. This article shows the historical evolution of public probity in Chile, emphasizing the ways several governments have dealt with the corruption issue since democratic restoration in 1990.